2013
DOI: 10.1530/eje-12-0775
|View full text |Cite
|
Sign up to set email alerts
|

The presence of thyroid peroxidase antibody of IgG2 subclass is a risk factor for thyroid dysfunction in chronic hepatitis C patients

Abstract: Objective: To investigate the prevalence of thyroid dysfunction (TD) and IgG subclasses of thyroid autoantibodies (TAs) and to determine the predictive factors of TD in chronic hepatitis C (CHC) patients. Design: Three hundred and twelve untreated hepatitis C virus-infected patients without a history of TD or treatment with thyroid hormones were enrolled in a cross-sectional study. Clinical and biological factors were statistically analyzed to determine the correlation between TD and this patient population. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
2
1
0
Order By: Relevance
“…According to our results, though overall incidence of TD was much higher than general population, pattern of relatively more hypothyroidism (9.0%) than hyperthyroidism (6.3%) was observed in HCV patients. This result is in accordance with other studies in which higher incidence of hypothyroidism as compared to hyperthyroidism is reported in HCV patients [15, 17]. According to a recent meta-analysis HCV patients are three times more prone to hypothyroidism as compared to control subjects [21].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…According to our results, though overall incidence of TD was much higher than general population, pattern of relatively more hypothyroidism (9.0%) than hyperthyroidism (6.3%) was observed in HCV patients. This result is in accordance with other studies in which higher incidence of hypothyroidism as compared to hyperthyroidism is reported in HCV patients [15, 17]. According to a recent meta-analysis HCV patients are three times more prone to hypothyroidism as compared to control subjects [21].…”
Section: Discussionsupporting
confidence: 92%
“…Our results showed that thyroid dysfunction was detected in 15.2% of the HCV patients. This figure is in accordance with studies carried out in other countries reporting thyroid dysfunction in 7% to 15% untreated HCV patients [68, 17]. A recent review of such studies reported 10–15% frequency of TD in interferon-free HCV patients [18].…”
Section: Discussionsupporting
confidence: 89%
“…These diseases have confirmed an increased prevalence among patients with thyroid disorders [5,6,7,8,9]. Based on the immunological pathogenesis of OLP, previous research has shown the presence of serum antibodies to thyroglobulin and thyroid microsomal antibodies in OLP patients [10,11].…”
Section: Introductionmentioning
confidence: 92%